Post-communist state measures to thwart organized labor: The case of Romania. (November 2015) - Varga, Mihai; Freyberg-Inan, Annette
This article supplements the literature on post-communist trade unions with an account of how state measures can affect union strength in post-communist Europe. The authors focus on the case of Romanian trade unions, which is exceptional in post-communist Europe in that it is possible to rule out lack of protest capacity as a cause for weakness of policy influence: Romanian unions have maintained a high protest capacity throughout the transition. However, this protest capacity has translated into influence over national economic policy and labor-relevant legislation only throughout the 1990s, and much less so in the 2000s and beyond. The authors examine the reasons for the trade unions' diminishing influence over national policies and observe a refinement of government measures to render protest ineffective. Key measures include a reduction of the unionized labor force, especially in protest-prone sectors, the de-coupling of plant-level protests from national mobilizations, the granting of selective concessions dividing organized labor, and, more recently, efforts to employ legal changes and state agencies to apply pressure on union leaders.